Transformasi Smart City Dalam Implementasi E-Government di Daerah Kepulauan - Hafel, Muhlis; Jamil, Julfi (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
This research was conducted to see the transformation of the Movement towards Smart City program in encouraging the implementation of E-Government in an archipelagic region to create effective, efficient, and accountable governance. This research used a qualitative approach and was conducted in South Halmahera Regency, North Maluku Province. In obtaining field data, researchers used interview instruments, observation, and documentation studies. While informants include OPD leaders, DPRD members, sub-district heads, and community leaders. Data analysis using the Spiral analysis technique. Based on data analysis, it was found that the South Halmahera Regency Government has transformed the Smart City program to encourage the implementation of E-Government in the form of Labuha Smart City service applications, but with the geographical condition of South Halmahera as an archipelago that has limited information technology infrastructure, the program carried out is still focused on two main services, namely Senyum Halsel which is related to government public services to the community and Go-Smile application services which are institutional information management systems that are still focused on the central government area of South Halmahera Regency. To encourage the acceleration of E-Government transformation to the fullest, it is necessary to have a commitment from the local government through the formation of local regulations that can encourage all elements to commit to the development of E-Government in the archipelago because the local government itself does not yet have binding regulations so that when there is a change in local leadership, it also changes the E-Government program.